Leucaena leucocephala as a green manure for bean growing in "Cerrado" soil - Chagas, José Mauro; Kluthcouski, João; Aquino, Antonio Renes Lins de (Pesquisa Agropecuaria Brasileira, 2014)
Two trials were undertaken for the purpose of evaluating leucaena (Leucaena leucocephala (Lam.) de Wit.) as a green manure in a Dark-Red Latosol under "cerrado" vegetation in the municipality of Goiânia, Goiás, Brazil. In the first trial, the green manure was seeded with spacing of 2, 3, 4 and 5 meters between rows, with 30 seeds/m. An analysis of growth showed an increase in the production of dry matter/ha and in nitrogen, phosphorus, potassium, calcium and magnesium, per sample, as spacing decreased. In the second trial, beans (Phaseolus vulgaris L.) were planted between the rows of leucena, after pruning of lateral shoots, leaving only the main stalk cut at a height of 1.5 m. Treatments consisted of the incorporation or non-incorporation of the leucena, combined with nitrogen (30 k/ha of N) or phosphorus (120 k/ha of P2O5) or nitrogen + phosphorus. The incorporation of leucena in the soil alone resulted in a production of beans equivalent to that of the treatments which received chemical fertilization.